Kinetic modeling of a heterogeneous Fenton-type oxidative treatment of complex industrial effluent - Covinich, Laura Gabriela (2018)
This work proposes a kinetic model for the reactions involved in the heterogeneous copper-based Fenton-type oxidation of mixed recalcitrant compounds in a real industrial effluent from the alkaline sulfite treatment of wood. This kind of treatment is unusual in this industry due to the complexity of the effluents and the high costs involved in total mineralization of the organic matter. Nevertheless, conversion of recalcitrant to degradable compounds and catalyst recovery can make the difference. The complexity of the effluent and the great number of compounds formed as intermediates, make extremely difficult the identification and quantification of the individual reactions that occur during oxidation. To solve this drawback TOC parameter was used as a representative measurement. To verify the level of TOC degradation produced by the heterogeneous catalysis reaction, experiences of homogeneous catalysis and adsorption were accomplished. The studied temperature range was 45–80 °C. A “two-step” kinetic model was applied to TOC reduction in heterogeneous and homogeneous oxidations, admitting two sequential steps of oxidation: a first fast stage (“seconds stage”) followed by a slow one (“minutes stages”). Kinetic constants were obtained for both processes and activation energies were also determined for the “minutes stage” step (33.17 kJ/mol and 15.13 kJ/mol, respectively). Homogeneous catalysis studies confirm mass transfer limitations in heterogeneous oxidations. Experiences of adsorption of organic matter on CuO/γ-Al2O3 catalyst demonstrated that this phenomenon is exothermic and cannot be neglected. The activation energy of adsorption was determined as 7.32 kJ/mol. Catalysts were characterized through SEM, EDS, XRD, FTIR, and TGA. Graphical Abstract: [Figure not available: see fulltext.].